Climate policy impacts on building energy use, emissions, and health: New York City local law 97. (1st January 2022) - Salimifard, Parichehr; Buonocore, Jonathan J.; Konschnik, Kate; Azimi, Parham; VanRy, Marissa; Cedeno Laurent, Jose Guillermo; Hernández, Diana; Allen, Joseph G.
Abstract: Climate policies increasingly focus on the building sector to reduce its energy and emission footprint, since building energy use is a major source of greenhouse gas (GHG) and air pollution emissions. The most ambitious climate policy focusing on the building sector is New York City (NYC)'s local law 97 (LL97). LL97 requires all mid-size and large buildings (>25, 000 ft 2 (2, 323 m 2 )) to reduce the GHG emissions associated with their energy use, 40% by 2030, and 80% by 2050. This study uses several models and regulatory datasets to build novel NYC building energy use and GHG emission profiles based on LL97 and to investigate the impacts of LL97 on energy, climate, and health. Results show that climate impacts of 2018 energy use in LL97-covered buildings is ∼$3.24 billion USD. The premature mortality due to exposure to 2017 NYC stationary fuel combustion emissions were 1.73–3.42K deaths ($19.9–39.2 billion USD). From this total premature mortality cases in stationary sectors (industry, electricity, and buildings), 0.838–1.87K deaths ($9.62–21.5 billion USD) were from buildings. To achieve emission reduction goals and enable beneficial building electrification, the grid should be decarbonized. Additionally, LL97's apparent exclusion of biomass is a key gap, with potentially adverse effects on health and broad implications for energy/climate policies. Biomass has an outsized adverse health impact; NYC biomass use alone caused 0.707–1.55K deaths ($8.12–17.8 billion USD) in 2017. Yet LL97 does not explicitly mention biomass, and may inadvertently incentivize the use of this fuel, for instance by enabling the use of renewable energy credits from biomass for compliance. This can lead to increased adverse health impacts from biomass combustion. Our findings demonstrate the necessity of including health in energy and climate policy design. Highlights: Combustion of gas and biomass are major sources of NYC air pollution mortality. NYC biomass use alone caused 0.7–1.5K deaths ($8.0–17.8 billion) in 2017. LL97 may enable continued biomass use leading to higher adverse health impacts. To achieve both electrification & LL97 goals, NYC grid should be swiftly decarbonized. Health should be central design criteria for climate policies.